Accountability of Corruption Perpetrators Who Have Returned Money from Corruption Funds (Case Study of Case No. 49/Pid.Sus TPK/2021/PN Mdn) - Viranti, Syahliza; Mulyadi, Mahmud; Sutiarnoto, Sutiarnoto (Universitas Medan Area, 2025)
This study aims to analyze the criminal responsibility of perpetrators of corruption who have returned state financial losses. Criminal responsibility in corruption crimes is regulated in Article 2 paragraph (1) and Article 3 of Law Number 31 of 1999 concerning the Eradication of Corruption. This study examines a corruption case with defendant Petrus Sabungan Hiras Fredy Aritonang Radjagukguk who was charged with committing a corruption crime with a state loss of Rp5,900,000,000, as decided in Decision Number 49/Pid.Sus-TPK/2021/PN Medan. In this case, the panel of judges at the first instance acquitted the defendant, even though the public prosecutor had filed a cassation appeal which was later rejected through Decision Number 2767 K/Pid.Sus/2022. The research method used is normative legal research with a statutory approach and case studies, which are sourced from primary and secondary legal materials through literature studies. This research is descriptive with qualitative data analysis. The results of the study indicate that the restitution of state financial losses does not eliminate the criminal liability of the perpetrator of corruption, but can only be used as a mitigating factor for the sentence, as stipulated in Article 4 of Law Number 31 of 1999. The court's decision in the a quo case is deemed not to fully reflect the spirit and objectives of eradicating corruption, because the judge's considerations have not optimally assessed the defendant's position, authority, and responsibility in the process of committing the unlawful act.